A Novel Photometric Method for Melamine Determination in Milk. - Supriyanto, Ganden (Fakultas Sains dan Teknologi Universitas Airlangga, 2011)
In this research, a spectrophotometric method for melamine determination in milk based on diazotitation reaction using reagent naphtylethilendiamine for melamine determination, to determine optimum reagent, and also to determine the proposed method validity. Sample of melaminewas reacted with NaNO2 and hydrochloride acid at low temperature to form diazonium salt and then was added with naphtylethilendiamine reagent to give a violet color complex. The absorbance was measured at 549 nm. The best result was found at the reagent concentration NaNO2 8.10-3 M, HCI 9 N and naphtylethilendiamine 8.10-5 M. Response time is very fast when the temperature was less than 15 C and in acid condition. But, the stability and durability of the color are low. the color is sharpeless and easily loss. Standart curve by addition standard method showed a good linearity with melamine concentration in the range of 8.10-6 up to 8.10-5 M, standard deviation and precision 0.0612 and 16.06%, limit of detection 2.21 ppm, sensitivity 640.4 L/mol and recovery 96.83%. Analysis of melamine added into the milk matrix yields the absorbance that is almost equal to the absorbance of melamine standard solution.